2017
DOI: 10.1590/s1679-45082017ao3870
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety in a case series of amyotrophic lateral sclerosis: frequency and association with clinical features

Abstract: Objective To investigate the frequency of anxiety and depression and their association with clinical features of amyotrophic lateral sclerosis.Methods This is a cross-sectional and descriptive study including a consecutive series of patients with sporadic amyotrophic lateral sclerosis according to Awaji’s criteria. Patients underwent clinical and psychiatric assessment (anxiety and depression symptoms).Results We included 76 patients. The men/women ratio was 1.6:1. Participants’ mean age at disease onset was 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 13 publications
1
8
0
2
Order By: Relevance
“…It was demonstrated that the occurrence of depression is more probable after an ALS diagnosis, more likely within one year after the onset of motor symptoms [ 11 , 25 ]. The prevalence of depression in our study is within the range reported by other studies [ 26 , 27 ]. The possible explanation for this high prevalence of depression at more than one year after ALS diagnosis is due to severe emotional and psychological distress when facing a no hope diagnosis, and on the other hand because of the physical disabilities that worsen over time.…”
Section: Discussionsupporting
confidence: 89%
“…It was demonstrated that the occurrence of depression is more probable after an ALS diagnosis, more likely within one year after the onset of motor symptoms [ 11 , 25 ]. The prevalence of depression in our study is within the range reported by other studies [ 26 , 27 ]. The possible explanation for this high prevalence of depression at more than one year after ALS diagnosis is due to severe emotional and psychological distress when facing a no hope diagnosis, and on the other hand because of the physical disabilities that worsen over time.…”
Section: Discussionsupporting
confidence: 89%
“…Two previous models proposed that anxiety and depression share the construct of negative affectivity, but differ with respect to the presence of neurophysiological arousal in anxious people and the lack of positive affectivity in depressed people. The high comorbidity of anxiety and depression in ALS, and the stronger correlation of depressive symptoms with trait anxiety rather than with state anxiety, foster the use of both STAI Form Y scales for grasping different facets of this construct.…”
Section: Discussionmentioning
confidence: 99%
“…The Hospital Anxiety and Depression Scale (HADS) and the anxiety subscale of the Brief Symptom Inventory (BSI) focus on state anxiety, i.e., on the current state of tension and apprehension, neglecting the distinction between state anxiety and dispositional/trait anxiety . Indeed, state anxiety in ALS might reflect a temporary, acute reaction to speech and swallowing difficulties, without clear association with disease duration or cognitive decline . Only a few studies have addressed trait anxiety (i.e., a generalized emotional predisposition to be anxious, careful, upset, nervous, and cautious) in ALS and have reported a prevalence rate 2–13% .…”
mentioning
confidence: 99%
“…Depressive symptoms were also frequent as 33% of patients had clinically relevant depressive symptoms according to HAD-depression. Depressive symptoms may be observed in bvFTD 22 and are commonly observed in ALS [23][24][25] . Here we found that depressive or anxiety symptoms may overlap with apathy and other bvFTD features in ALS.…”
Section: Discussionmentioning
confidence: 99%